2017
DOI: 10.1016/j.ymthe.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

A Rational Strategy for Reducing On-Target Off-Tumor Effects of CD38-Chimeric Antigen Receptors by Affinity Optimization

Abstract: Chimeric antigen receptors (CARs) can effectively redirect cytotoxic T cells toward highly expressed surface antigens on tumor cells. The low expression of several tumor-associated antigens (TAAs) on normal tissues, however, hinders their safe targeting by CAR T cells due to on-target/off-tumor effects. Using the multiple myeloma (MM)-associated CD38 antigen as a model system, here, we present a rational approach for effective and tumor-selective targeting of such TAAs. Using "light-chain exchange" technology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
223
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(235 citation statements)
references
References 41 publications
(75 reference statements)
6
223
0
Order By: Relevance
“…As for TCRs, the choice of antigen is crucial to prevent offtarget effects, which can even be fatal [99,100]. This undesirable behavior may be mitigated for example by modulating the antibody affinity [101,102], by pairing high affinity heavy chains derived from a defined antibody to various light chains [103] or by mutating the signaling moiety [104].…”
Section: Car Basic Structural Principal and Determinant Of Functionmentioning
confidence: 99%
“…As for TCRs, the choice of antigen is crucial to prevent offtarget effects, which can even be fatal [99,100]. This undesirable behavior may be mitigated for example by modulating the antibody affinity [101,102], by pairing high affinity heavy chains derived from a defined antibody to various light chains [103] or by mutating the signaling moiety [104].…”
Section: Car Basic Structural Principal and Determinant Of Functionmentioning
confidence: 99%
“…The relationship between binding affinity and efficacy is more nuanced in the context of CARs as compared with mAbs, for which higher affinity is typically desirable. For example, on the basis of observations from preclinical studies, whereas a receptor tyrosine kinase-like orphan receptor 1 (ROR1)-CAR derived from a high-affinity scFv (with a dissociation constant of 0.56 nM) resulted in increased therapeutic index when compared with a lower-affinity variant [28][29][30] , other examples have reported that engineering the scFv for lower affinity improves the discrimination among cells with varying antigen density [31][32][33] , which could be useful for enhancing the therapeutic window for antigens differentially expressed on tumour versus normal tissues. However, this approach might increase the risk of immune evasion, owing to the emergence of low-antigen-expressing tumour cells.…”
Section: Review Articlementioning
confidence: 99%
“…79 The basis for this approach is that MM cells express higher levels of CD38 than most normal hematopoietic cells. 78,79 In addition to optimizing scFv affinity, Drent et al and Straathof et al have constructed anti-CD38 CAR-Ts with caspase-9-based suicide genes to eliminate CAR-Ts on demand.…”
Section: Cd38mentioning
confidence: 99%